Concept of "absolute right" of G. Hegel in modern changing world - Харченко, С. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
The phenomenon of "absolute law" as a basic principle in the architecture of universal moral and ethical paradigms, as well as modern institutional and legal systems is conceptualized in the study. The key task of the study was to measure the "absolute" – "right" relevance in the pan-logical philosophical and legal paradigm of G. Hegel’s discourse. The philosophical-legal and philosophical-historical approaches to compare the philosopher’s fundamental positions, representing law as a social norm and a moral will, as well as to check their compatibility in historical and logical discourses were used. Hermeneutic method allowed interpreting G. Hegel’s texts, which resulted in the correct use of key categories of "law", "right", "moral," "morality." As a result of the study it was confirmed that G. Hegel’s concept of "absolute law" is based on the idea of self-development of the absolute purpose of the Will as an ascent to Good, which ultimate link is the realization of the truth of Good. And only then it will be able to come close to absolute knowledge. At the climax of its development, it comprehends an absolute Idea. Absolute law becomes conscious at the center of its self and free, capable of infinite self-development. Absolute right is the embodiment of the "pure idea of freedom". Absolute right is identical to the Absolute Spirit.